Evaluación del efecto blanqueador de tres pastas dentales. revisión bibliográfica - Rosero Flores, Leslie Yajaira (2025)
Introduction: The desire for an aesthetic smile has become one of the top priorities for people, but, the color of teeth can be altered by pigments, chromogenic substances, etc. To lighten the color of teeth, toothpastes have been developed and are widely used by individuals and health professionals. However, their whitening effectiveness has not been properly studied. Objective: To identify the whitening effectiveness of Colgate Luminous White, Crest Peroxide and Sensodyne Whitening Repair & Protect whitening toothpastes by means of a systematic review to determine which is the best toothpaste to use as a teeth whitening treatment. Materials and methods: A qualitative, applied and descriptive research approach that used a documentary review method to obtain scientific articles related to the subject of the study in the PubMed, ScienceDirect and LILACS databases. Keywords and inclusion and exclusion criteria were used. Results: A total of 189 documents were found, of which only 11 were selected as having valid information for the research. Conclusion: It is concluded that Crest Peroxide toothpaste has a better whitening action compared to the other two toothpastes studied, since Colgate Luminous White, Sensodyne Whitening Repair & Protect presented very similar whitening effectiveness, so Crest Peroxide is recognized as the best toothpaste that can be used as a tooth whitening treatment.